STUDENTS’ PERCEPTION TOWARDS THE USE OF VIDEO IN ENGLISH CLASS - Silvia Revansyah; Efransyah (PROJECT (Professional Journal of English Education), 2023)
The aim of this study is to comprehend how students feel about using videos in English classes. The research technique makes use of qualitative research. 32 students completing English lessons participated in this study. The study used a Likert scale, which included two response choices: "agree" and "disagree." The study issues were addressed using 7 questionnaire items. The results demonstrate students' favourable attitudes towards videos, and all variables strongly influenced use intention. Videos can be used in a range of active learning contexts to foster a positive, sociable, and cooperative learning environment while also increasing student motivation and involvement. The use of audiovisual materials in the classroom seems to be appealing to students, who understand digital tools and technologies.